Age‐related decline in BubR1 impairs adult hippocampal neurogenesis. Issue 3 (6th April 2017) - Yang, Zhongxi; Jun, Heechul; Choi, Chan‐II; Yoo, Ki Hyun; Cho, Chang Hoon; Hussaini, Syed Mohammed Qasim; Simmons, Ambrosia J.; Kim, Seonhee; van Deursen, Jan M.; Baker, Darren J.; Jang, Mi‐Hyeon
Summary: Aging causes significant declines in adult hippocampal neurogenesis and leads to cognitive disability. Emerging evidence demonstrates that decline in the mitotic checkpoint kinase BubR1 level occurs with natural aging and induces progeroid features in both mice and children with mosaic variegated aneuploidy syndrome. Whether BubR1 contributes to age‐related deficits in hippocampal neurogenesis is yet to be determined. Here we report that BubR1 expression is significantly reduced with natural aging in the mouse brain. Using established progeroid mice expressing low amounts of BubR1, we demonstrate these mice exhibit deficits in neural progenitor proliferation and maturation, leading to reduction in new neuron production. Collectively, our identification of BubR1 as a new and critical factor controlling sequential steps across neurogenesis raises the possibility that BubR1 may be a key mediator regulating aging‐related hippocampal pathology. Targeting BubR1 may represent a novel therapeutic strategy for age‐related cognitive deficits.